2011
DOI: 10.3111/13696998.2011.598200
|View full text |Cite
|
Sign up to set email alerts
|

Mail-order pharmacy use and medication adherence among Medicare Part D beneficiaries with diabetes

Abstract: Adherence with oral anti-diabetic medications among Medicare Part D beneficiaries is suboptimal. Patients using mail-order pharmacy had better adherence to oral anti-diabetic medications than those who used retail pharmacies. However, the causal relationship between mail-order pharmacy use and adherence should be further examined in a randomized study setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
4
39
0
1
Order By: Relevance
“…35–39 This study provides additional evidence that exposure to mail order pharmacy across racial and ethnic subgroups, rather than differential response to this practice, contributes to disparities in adherence. 36 However, it is important to note that all patients using mail order pharmacy in this setting also had access to telephone based counseling from pharmacists and approximately one-third also received a financial incentive (i.e., lower copays) for participating in the program.…”
Section: Discussionmentioning
confidence: 85%
“…35–39 This study provides additional evidence that exposure to mail order pharmacy across racial and ethnic subgroups, rather than differential response to this practice, contributes to disparities in adherence. 36 However, it is important to note that all patients using mail order pharmacy in this setting also had access to telephone based counseling from pharmacists and approximately one-third also received a financial incentive (i.e., lower copays) for participating in the program.…”
Section: Discussionmentioning
confidence: 85%
“…Barriers for optimal adherence to treatments for T2D could be due to regimen complexity. Studies examining the association between anti-diabetes medication regimen complexity and anti-diabetes medication adherence have shown that regimens with less frequent dosing are associated with increased adherence [34, 35]. However, adherence to treatments after a certain period of time is similar for orals and injectables, so lack of adherence may not be solely based on regimen complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Stuart et al 25 —using 2006 claims data from a random 5% file of Medicare beneficiaries (n = 45,613 PDP enrollees) and from retiree health plans (n = 211,919)—found no statistical difference between PDP and retiree health plan enrollees in medication possession ratios or duration of most therapies for diabetes. Using 2008–2009 claims data (n = 22,546), Zhang et al 26 reported that only 42% of all respondents attained adherence with oral antidiabetic medications but that adherence rates were higher among respondents using mail-order pharmacies than those using walk-in pharmacies (49.7% vs 42.8%). Additionally, 3 studies examined antidepressant/antipsychotic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Although the net effects of Part D are overall decreases in CRN and nonpersistence, 20,21 additional interventions may be necessary to target beneficiaries with certain health conditions, including ESRD, 24 diabetes, 26 and psychosis. 29 Before the coverage gap is phased out (by 2020), providers should closely monitor CRN and drug discontinuation during the gap to avoid potential adverse clinical consequences, 22 especially in patients on osteoporosis treatments.…”
Section: Resultsmentioning
confidence: 99%